Unlocking Better Reading Skills: How Multimedia and Interactive Tools Make a Difference - Nurhasanah, Indri; Firdaus, Masagus (LPPPI Publishing, 2025)
Using multimedia and interactive tools in reading instruction has become more popular as a way to improve student engagement and understanding in an increasingly digital educational environment. The effectiveness of these digital resources which include interactive apps, educational games, and e-books in enhancing reading abilities across a range of learner profiles is investigated in this paper. This study synthesizes information from 35 peer-reviewed articles published between 2020 and 2024 using a qualitative research methodology. The review demonstrates the potential of multimedia technologies to create a more dynamic learning environment by highlighting important advantages including improved motivation, comprehension, and differentiation of instruction. The study does, however, also address some significant shortcomings, such as teacher readiness, content quality, equity concerns, cognitive overload, and reliance on technology. In order to optimize learning outcomes, these criteria highlight the need for thorough educator training and fair access to digital resources. This article offers insightful information for educators and government official who want to incorporate technology in a way that promotes reading development by outlining both its advantages and disadvantages. The results imply that although multimedia tools have the potential to revolutionize literacy instruction, their application needs to be carefully considered to guarantee the best possible learning outcomes.